Volumetry Reality Augmented Reality Application with Android Based Marker Based Tracking Method - Tri Ika Jaya Kusumawati (Universitas Negeri Medan, 2022)
Volumetry reality is an application that implements AR with an android-based marker based tracking method for presenting spatial learning materials. Learning to build space and mathematics is still an obstacle in its presentation, delivery and understanding, and the Covid-19 pandemic has forced students to study independently. This encourages educational staff to innovate in providing learning media. Volumetry reality is built by applying AR technology with a marker based tracking method, in this case it is presented in the form of a handbook intended for elementary and junior high school levels. It is designed attractively and easy to use and is equipped with a calculator and mini quiz. Volumetry reality is built using unity and the Vuforia SDK (Software Development Kit). This application can be used by scanning and producing 3D objects up to a distance of 50cm and can be used in low light.